Trend in Tyrosine Kinase Inhibitor Utilization, Price, and Out-of-Pocket Costs in Patients With Chronic Myelogenous Leukemia. Issue 11 (November 2021) - Talon, Brian; Calip, Gregory S.; Lee, Todd A.; Sharp, Lisa K.; Patel, Pritesh; Touchette, Daniel R.
Abstract : PURPOSE: Treatment of chronic myelogenous leukemia (CML) with tyrosine kinase inhibitors (TKIs) has improved survival but is associated with significant financial burden. We measured the annual trend in TKI utilization, Medicare gross payment, and patient out-of-pocket (OOP) expenditure from 2007 to 2016. METHODS: We used SEER linked to Medicare part-D claims data to identify prevalent CML cases from 2007 to 2016. TKI utilization was measured as the proportion of cases with at least one TKI fill in each year. Average TKI gross payment and median per-member per-month OOP expenditure were calculated from claims data and plotted annually from 2007 to 2016. Year-to-year percent change in gross payment and OOP expenditure was compared with inflation indices. RESULTS: The cohort included 3, 189 CML cases with at least one TKI claim. The proportion of prevalent patients with a TKI fill in a year increased from 17.9% in 2007 to 52.8% in 2015. The average annual gross payment per 30-day supply of a TKI increased by an average of 12.8% throughout the period from 9, 000 to 10, 000 US dollars in 2016. There was no increasing trend in median OOP expenditure per 30-day supply, which varied between 450 and 600 US dollars. CONCLUSION: Rising TKI use and TKI drug prices place considerable financial pressure on Medicare part-D insurers. Although there was no increasing trend in OOP expenditure, it may be burdensome for Medicare patients who are likely retired on a fixed income. Our findings support legislation that mitigates increasing drug prices to protect the Medicare system and its beneficiaries.